What happened to the protests? The surprising lack of visible dissent during the Sochi Winter Olympics. Issue 4 (3rd April 2017) - Ekberg, Johan; Strange, Michael
Abstract: In the build-up to the Sochi Olympics, there was substantial anticipation that its legacy would be dominated by dissent and political controversies rather than gold-winning performances. Yet, when the torch was lit, far fewer of those expected controversies ignited. In turning to International Relations theory (IR), the article argues the Sochi Olympics evidenced a tension between, on one hand, a tight process of political management by Russian state representatives, the organizing committee and the International Olympic Committee, whilst on the other hand utilizing certain key norms to help ensure consent. Utilizing a Social Constructivist emphasis on norms as key tools for conducting global politics, the analysis shows how that tension incorporated well-recognized ideas from both the IR schools of Realism and Liberalism to silence protesters. In evidencing the value-added of drawing upon other schools of thought outside conventional sports analysis, the article illustrates a new way for conducting research in Olympic studies.